Information System For Filing Deed Data (Sidak) At The Population And Civil Registry Office Of Kabupaten Purwakarta - Eka Chandra Ramdhani; Onyx Dewi Quraesin; Asep Asep; Juniarti Eka Sapitri; Fransisca Natalia (Journal of Information System, Informatics and Computing, 2022)
Archiving is a mechanism for storing various forms of documents in various formats so that they are safe and can be accessed again within a certain period of time. The function of data archiving is to support administrative activities, decision making tools, evidence of accountability, sources of information and as a vehicle for communication. At the Department of Population and Civil Registry of Purwakarta Regency in archiving deed data it is still not optimal because of the limited role of information technology so that archival data control does not run effectively, efficiently and systematically. This study uses the waterfall method to develop the system, the waterfall method is a method that starts with a survey to the design of the application, each stage is carried out systematically from the analysis stage to the last stage, namely system maintenance. The Deed Data Archiving information system which is designed aims to build an information system to make it easier for the Population and Civil Registry Office to carry out Deed Data Archiving easily and produce an effective, efficient and systematic filing system.